(3Zfj hefj aj GdWHs - (3GdMSf Hf fhM GdbeQj GdMcje, CHh efUhQ,J (B380 (3g` s
(3ChdgG (B:s
(3bGd CHh efUhQ , GdMSf Hf fhM GdbeQi(B: (3Efj de GRd aj UHGj , hefP YbdJ GMH GdYdhe GdWHjYjI hJfGRYfi faSi EdjgG hNUhUkG Yde GdWH s
(3BNQgG (B:s
(3EdG Gf GdPi Hbi cKQ ef GdPi CKHJ, hajeG CKHJ , hHg HdGZ GdcaGjI aj HGH GdYdGL hGdeOGhGI hddg GdPi Cdgefi gPG GdYde hhbafi dg , GdMeO hGdefI s
(3GdeDda cGf MjkG bHd SfI (B428 (3g`s
(3GfXQ agQS GdWH Qbe(B155 (3HYfhGfGdTeSjI GdefUhQjIs
(3fSNI QGHYIs
(3hoJSei ZfGA aj GdWHs
(3hoJSei CjVkG GdTeSjI GdefUhQjIs
(3hHChdgG agQSJ WZJ GdXdeI Ydi UaMGJg s
Keywords: (3GdWHs